Investment Criteria, Productivity and Economic Development: An Empirical Comment - Ranis, Gustav (Quarterly Journal of Economics, 1962)
Journal Article Investment Criteria, Productivity and Economic Development: An Empirical Comment Get access Gustav Ranis Gustav Ranis Yale University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 76, Issue 2, May 1962, Pages 298–302, https://doi.org/10.2307/1880821 Published: 01 May 1962